Spectrophotometric Determination of Sulphameter with N-1-(Naphthyl) Ethylenediamine Reagent by Using Diazotization Coupling Reaction - Amal H. Mhemeed (Journal of Global Pharma Technology, 2016)
Cutting edge method of spectrophotometric for the assay of micro amount of sulphameter  The method is based  on the reaction of sulphameter in acidic medium with sodium nitrite to form the diazonium  ion which is coupled with N-1-(naphthyl) ethylenediamine to form a stable a pinkish- red  azo dye which shows maximum absorption at 503 nm. Beer’s law is obeyed over the concentration range 0.2 – 14 ppm. The molar absorptivity is (5.21 ´ 104) l.mol-1.cm-1, Sandal sensitivity index of (5.23 ´ 10-3) mg.cm-2. With a relative error of (-0.05% - + 2.3%) and relative standard deviation of (± 0.02% - ± 1.5%). The present method requires neither temperature control nor solvent extraction step.Keywords: Sulphameter drug, N-1-(naphthyl) ethylenediamine, Spectrophotometric Determination.